Evaluation of Antibacterial and Cytotoxic Potency of Polyherbal Gel Formulation Containing Achyranthes Aspera and Trachyspermum Ammi as Intracanal Medicament: An In Vitro Study - Ram Surath Kumar; Anil V. Ankola; Mahantesh B. Nagamoti; Roopali M. Sankeshwari; Kishori P. Sutar; Shushant I Jigan; Atrey Pai Khot; Ritiha Uppin (Journal of Dentistry)
Background: The overwhelming increase of antibiotic-resistant bacteria, and the adverse reactions of using synthetic drugs such as chlorhexidine (CHX) and calcium hydroxide (Ca(OH2))- based intracanal medicaments have made it mandatory to search for effective substitutes. Herbal medicines like Achyranthes aspera (A.aspera) and Trachyspermum ammi (T.ammi) have been used in many clinical conditions and it appears to be a distinct material next to Ca(OH2) in the field of dentistry.Purpose: Evaluate the antibacterial potential and cytotoxic effects of novel polyherbal gel containing A.aspera and T.ammi, CHX gel, and Ca(OH2) paste based intracanal medicaments in root canal treatment against Enterococcus faecalis (E.faecalis).Materials and Method: In this in vitro study, Ethanolic extracts of A.aspera and T.ammi were prepared by the Soxhlet apparatus method. The individual plant extracts and the plant extract mixtures (1:1, 2:1, and 1:2), CHX, and Ca(OH2) were assessed for minimum inhibitory concentration (resazurin microtiter assay), fractional inhibitory concentration and minimum bactericidal concentration (spread plating method) against E.faecalis. The polyherbal intracanal medicament was assessed for zone of inhibition (well diffusion method) and cytotoxicity (MTT assay) on human periodontal ligament cells. All experiments were performed in triplicate.Results: Polyherbal gel containing A.aspera and T.ammi, CHX gel, and Ca(OH2) paste-based intracanal medicaments showed statistically significant antibacterial activity (p <0.05) against E.faecalis with CHX showing superior properties followed by polyherbal gel. The results of the cytotoxicity assay demonstrated the good biocompatibility of the polyherbal intracanal medication, which exhibited 95.13% of surviving cells.Conclusion: The use of herbal alternatives as an intracanal medicament proved to be advantageous considering the several undesirable characteristics of CHX and Ca(OH)2.